"The internet and the European market" from a multidisciplinary perspective: a "round-doc" discussion. Issue 2 (2nd April 2020) - Schafer, Valérie; Fickers, Andreas; Howarth, David; Musiani, Francesca; Pohle, Julia; Winseck, Dwayne
Abstract: David Howarth, Francesca Musiani, Julia Pohle and Dwayne Winseck were invited to discuss the main topic of this special issue, "The internet and the EU market." This conversation at the crossroads of several research areas (communication studies, sociology, science and technology studies and political science) brought together leading experts who shared their experience, research and expertise on the internet, European integration, governance issues, etc. They referred to several topics that are addressed in the papers in this issue, such as the taxation of digital services, net neutrality and the openness of networks, as they discussed questions related to the realities and limits of the notion of "Digital Europe", changing discourses on the EU's digital economy, the concept of European governance and the turning points and key events in the relationship between the internet and the EU market since the 1990s.